The Use of The Wordwall Game in Integer Arithmetic Operations to Increase The Mathematics Learning Interest of Fifth-Grade Students - Jessica Dhiya‘ Ulhaq; Muhammad Ya’ban Zakiya; Diana Ermawati (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This research was conducted to increase interest in learning mathematics by using a wordwall for integer calculation operations. This research was carried out at SD Negeri 3 Sidigede with the research subjects being students. The data collection techniques used in this research were observation and interviews in the form of questionnaires. The data analysis technique used is the Miles and Huberman interactive technique which includes data reduction, data presentation and drawing conclusions. This research uses the PTK method which consists of 2 cycles based on the Mcel Kemmis and Mc Taggart models. The results of the research show that there is an influence on the learning interest of class V students at SD Negeri 3 Sidigede, indicated by an increase in the percentage of the student interest indicator, obtaining a percentage of 76.5% in cycle I and 84.57% in cycle II. The use of wordwall greatly influences students' interest in learning mathematics because it uses fun media so that students are interested in learning.